Solving first order nonlinear fuzzy differential equations using Optimal Homotopy Asymptotic Method - Jameel, A.F.; Saaban, Azizan; Altaie, S.A.; Anakira, N.R.; Alomari, A.K.; Ahmad, N. (Academic Publications, Ltd., 2018)
In this paper, we discuss the approximate solution of first order nonlinear fuzzy initial value problems (FIVP) by formulate and analyze the use of the Optimal Homotopy Asymptotic Method (OHAM).OHAM allows for the solution of the fuzzy differential equation to be calculated in the form of an infinite series in which the components can be easily computed.This method provides us with a convenient way to control the convergence of approximation series.Numerical examples using the well-known nonlinear FIVP are presented to show the capability of the this method in this regard and the results are satisfied the convex triangular fuzzy number.